Peptides mediating DNA transport on microtubules and their impact on non-viral gene transfer efficiency. Issue 5 (17th October 2017) - Midoux, Patrick; Pigeon, Lucie; Gonçalves, Cristine; Pichon, Chantal
Abstract : Synthetic vectors such as cationic polymers and cationic lipids remain attractive tools for non-viral gene transfer which is a complex process whose effectiveness relies on the ability to deliver a plasmid DNA (pDNA) into the nucleus of non-dividing cells. Once in the cytosol, the transport of pDNAs towards the nuclear envelope is strongly impaired by their very low cytosolic mobility due to their large size. To promote their movement towards the cell nucleus, few strategies have been implemented to exploit dynein, the microtubule's (MT's) motor protein, for propagation of cytosolic pDNA along the MTs towards the cell nucleus. In the first part of this review, an overview on MTs, dynein, dynein/virus interaction feature is presented followed by a summary of the results obtained by exploitation of LC8 and TCTEL1 dynein light chain association sequence (DLC-AS) for non-viral transfection. The second part dedicated to the adenoviral protein E3-14.7K, reports the transfection efficiency of polyplexes and lipoplexes containing the E3-14.7K-derived P79-98 peptide linked to pDNA. Here, several lines of evidence are given showing that dynein can be targeted to improve cytosolic pDNA mobility and accumulate pDNA near nuclear envelope in order to facilitate its transport through the nuclear pores. The linkage of various DLC-AS to pDNA carriers led to modest transfection improvements and their direct interaction with MTs was not demonstrated. In contrast, pDNA linked to the P79-98 peptide interacting with TCTEL1 via a cytosolic protein (fourteen seven K-interacting protein-1 (FIP-1)), interaction with MTs is evidenced in cellulo and transfection efficiency is improved.